YBa2Cu3O7 nano superconducting quantum interference devices on MgO bicrystal substrates. Issue 9 (26th February 2020) - Lin, Jianxin; Müller, Benedikt; Linek, Julian; Karrer, Max; Wenzel, Malte; Martínez-Pérez, Maria José; Kleiner, Reinhold; Koelle, Dieter
Abstract : We achieve ultra-low excess noise in nanoSQUIDs from the high-transition temperature cuprate superconductor YBa2 Cu3 O7 on a low-microwave-loss substrate. Abstract : We report on nanopatterned YBa2 Cu3 O7− δ (YBCO) direct current superconducting quantum interference devices (SQUIDs) based on grain boundary Josephson junctions. The nanoSQUIDs are fabricated by epitaxial growth of 120 nm-thick films of the high-transition temperature cuprate superconductor YBCO via pulsed laser deposition on MgO bicrystal substrates with 24° misorientation angle, followed by sputtering of d Au = 65 nm thick Au. Nanopatterning is performed by Ga focused ion beam (FIB) milling. The SQUID performance is comparable to devices on SrTiO3 (STO), as demonstrated by electric transport and noise measurements at 4.2 K. MgO has orders of magnitude smaller dielectric permittivity than STO; i.e., one may avoid Au as a resistively shunting layer to reduce the intrinsic thermal flux noise of the nanoSQUIDs. However, we find that the Au layer is important for avoiding degradation during FIB milling. Hence, we compare devices with different d Au produced by thinning the Au layer via Ar ion milling after FIB patterning. We find that the reduction of d Au yields an increase in junction resistance, however at the expense of a reduction of the critical current and increase in SQUID inductance. This results in an estimated thermal flux noise that is almost independent of d Au . However, for two devices on MgO with 65 nm-thick Au, we find an order of magnitude lower low-frequency excess noise as compared to nanoSQUIDs on STO or those on MgO with reduced d Au . For one of those devices we obtain with bias-reversal readout ultra-low flux noise of ∼175 n Φ 0 Hz −1/2 down to ∼10 Hz.